2016
DOI: 10.7554/elife.20320
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on adult human height across birth cohorts from 1886 to 1994

Abstract: Human height variation is determined by genetic and environmental factors, but it remains unclear whether their influences differ across birth-year cohorts. We conducted an individual-based pooled analysis of 40 twin cohorts including 143,390 complete twin pairs born 1886–1994. Although genetic variance showed a generally increasing trend across the birth-year cohorts, heritability estimates (0.69-0.84 in men and 0.53-0.78 in women) did not present any clear pattern of secular changes. Comparing geographic-cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 30 publications
3
42
1
Order By: Relevance
“…Since unique environmental variation also increased, only minor and unsystematic differences were found in the heritability of BMI. It is noteworthy that similar secular change in the genetic and environmental variances in height were not found, even though mean height also increased during the 20 th century (Jelenkovic et al, 2016b). This shows that there is no link between mean and variance in the anthropometric traits in general, and this result is specific to BMI.…”
Section: Factors Modifying Heritability Estimatesmentioning
confidence: 81%
“…Since unique environmental variation also increased, only minor and unsystematic differences were found in the heritability of BMI. It is noteworthy that similar secular change in the genetic and environmental variances in height were not found, even though mean height also increased during the 20 th century (Jelenkovic et al, 2016b). This shows that there is no link between mean and variance in the anthropometric traits in general, and this result is specific to BMI.…”
Section: Factors Modifying Heritability Estimatesmentioning
confidence: 81%
“…4 Body height has been shown to have a strong genetic component with around 80% of the variation in populations being explained by genetic differences between individuals. 5,23,24 The genetic component of height has furthermore been found to be consistent across countries independent of living standards. 5 Interestingly, we found that the estimate for the relationship between body height and dementia was greater in the within-pair analyses than in the cohort analysis of brothers.…”
Section: Findings In Light Of Previous Studiesmentioning
confidence: 94%
“…5,23,24 The genetic component of height has furthermore been found to be consistent across countries independent of living standards. 5 Interestingly, we found that the estimate for the relationship between body height and dementia was greater in the within-pair analyses than in the cohort analysis of brothers. Because the genetic variation in body height is smaller within brothers than between men in general, the results could be explained by genetic contribution to differences in body height between unrelated men that is not contributing to the differences in risk of dementia and thereby dilutes the association.…”
Section: Findings In Light Of Previous Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…vary in people belonging to different populations and ethnicities due to differences in genetics, 5 nutrition and levels of physical activity. 6,7,8 Studies have been conducted in many different parts of the world to estimate the stature from the measurements of various body parts.…”
mentioning
confidence: 99%